If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 3y + 1 = 0 Reorder the terms: 1 + -4x + 3y = 0 Solving 1 + -4x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -4x + -1 + 3y = 0 + -1 Reorder the terms: 1 + -1 + -4x + 3y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -4x + 3y = 0 + -1 -4x + 3y = 0 + -1 Combine like terms: 0 + -1 = -1 -4x + 3y = -1 Add '-3y' to each side of the equation. -4x + 3y + -3y = -1 + -3y Combine like terms: 3y + -3y = 0 -4x + 0 = -1 + -3y -4x = -1 + -3y Divide each side by '-4'. x = 0.25 + 0.75y Simplifying x = 0.25 + 0.75y
| 2x+30=140 | | 3(5c-1)(-2)=13c+3 | | 2x+80=140 | | 8x+2=8(x-8) | | -2x-3-5x=2(x-1) | | 2x+20=140 | | 15x^2+47x+28=0 | | 4x+12=42-x | | 3(5c-1)(-2)=13c+c | | Y=7x+265 | | X^2+14x+130=0 | | 7x-1=6+6x | | (4x-3y)(4x+3y)= | | 49.95=45.50 | | 2a-7=9-8-4a+5a | | 5(2x+3)-3(4x-1)=12 | | 3(-2x-2)=x+3 | | (a-8/12)=(2a+5/3) | | -6x+3=18 | | 6/16= | | 15(x-3)=-8-7 | | 7x+4-5=7y-8 | | (4t^2-t-9)(4t^2+4t-1)= | | x^2+2.25-36=0 | | 60+10x=5(x+20) | | -3(c-6)=-3-6 | | -5x-7=2x+14 | | 3x-7-5x=3-4x | | 4(a-3)=8a-(4a+12) | | 3[3u-6]=18 | | 14x+2x=-6-3x | | (3x-4)(5x^2-2x+6)= |